A Performance Analysis of VPN Technologies Used in an IoT Environment - HRITCAN, D.-F.; GRAUR, A.; BALAN, D. G.; TIMOFTE, E. M. (Advances in Electrical and Computer Engineering, 2025)
Internet of Things (IoT) devices face exponential growth daily across diverse sectors. The need for robust security measures to safeguard sensitive data and ensure privacy is imminent. Virtual Private Network (VPN) services emerge as a promising solution, offering encryption protocols to fortify communication channels and secure remote access to IoT devices. This research conducts a review and a performance evaluation of four prominent VPN services: OpenVPN, WireGuard, being the most common on the market, and Tailscale and ZeroTier, because they can function without access to a public IP address. The main goal is to fortify IoT environments. Exploring their performance parameters, encompassing metrics such as the transfer speed test and latency. The empirical findings from this experiment provide valuable insights into the intricate balance between security, performance, and operational feasibility of these VPN solutions in real-world IoT deployments. This nuanced understanding equips IoT security stakeholders and network administrators with the knowledge to make well-informed decisions about IoT security architecture and infrastructure optimization. Index Terms--IoT, OpenVPN, Tailscale, Wireguard, ZeroTier One.